Integration Of Pesantren Values In The Construction Of A Religious Society: A Study Of Local Government Policy In Bondowoso Regency - Rifa'i Rifa'i; Rusydi Rusydi (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study analyzes the institutionalization of pesantren (Islamic boarding school) values within regional governance to construct a religious society. Using a qualitative ethnographic case study, the research explores how local government policies transform traditional religious ethics into formal legal frameworks. Data were gathered through participant observation, document analysis, and in-depth interviews with cross-sectoral stakeholders, including legislative leaders, executive bureaucrats, and spiritual authorities. Findings reveal that the integration of pesantren values transcends symbolic programming, manifesting as a hybrid governance model that synergizes bureaucratic rationality with transcendental authority. The formalization of these values into local legislation has reconfigured public compliance, where civic duty now intersects with spiritual loyalty. This process facilitates a "collective habitus" that projects pesantren ethics into the public sphere (from pesantren to polis). Theoretically, this research proposes the “Triangle of Authority” paradigm—a conceptual framework connecting legal-rational governance, charismatic-religious leadership, and socio-cultural identity. This study argues that the sustainability of religious-based public policy depends on the state’s ability to synchronize formal instruments with the ethical gatekeeping of religious elites. These insights offer a significant contribution to the discourse on state-religion synergy and character education policy in contemporary Muslim-majority societies.